Continuity of Academic Intrinsic Motivation from Childhood through Late Adolescence: A Longitudinal Study - Gottfried, Adele Eskeles; Fleming, James S; Gottfried, Allen W (Journal of educational psychology, 2001)
Examines two aspects of continuity, stability of individual differences and means, in a study from the middle elementary through high school years. Two hypotheses were supported: academic intrinsic motivation is a stable construct through these years, and with advancement in age, academic intrinsic motivation becomes increasingly stable. (Contains 58 references, 2 tables, and an appendix.) (GCP)